1996
DOI: 10.1111/1523-1747.ep12298282
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Protoporphyrin IX in Plaque Psoriasis After Topical Application of 5-Aminolevulinic Acid Indicates a Potential for Superficial Photodynamic Therapy

Abstract: The success reported for the treatment of superficial skin carcinomas by photodynamic therapy with topical application of the photosensitizer precursor 5-aminolevulinic acid has therapeutic implications for the treatment of other skin disorders. This paper describes the accumulation of the photosensitizing agent protoporphyrin IX in areas of plaque psoriasis by monitoring of the fluorescence emission induced by low-intensity laser excitation at 488 nm. We present results from 15 patients with a total of 42 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 11 publications
7
51
1
Order By: Relevance
“…Fluorescence studies on the kinetics of the ALA-induced porphyrins showed maximum levels in BCC and PS 4-6 h after ALA application with 3-15-fold higher levels than in normal skin (Svanberg et al, 1994;Stringer et al, 1996). These data are supported by our analysis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Fluorescence studies on the kinetics of the ALA-induced porphyrins showed maximum levels in BCC and PS 4-6 h after ALA application with 3-15-fold higher levels than in normal skin (Svanberg et al, 1994;Stringer et al, 1996). These data are supported by our analysis.…”
Section: Discussionsupporting
confidence: 87%
“…In general, the available data on ALA-induced porphyrin levels in human tissues are based on fluorescence studies Svanberg et al, 1994;Szeimies et al, 1994;Malik et al, 1995;Martin et al, 1995;Peng et al, 1995;Stringer et al, 1996) (Table 4) and only some biochemical studies were performed (Fritsch et al, 1997c(Fritsch et al, , 1998. It was shown by fluorescence microscopy that the major factor limiting the efficacy of topical ALA-PDT is the penetration depth of ALA and ALA-induced NS 4.7 ± 0.8 88.3 ± 2.8 0 ± 0 0.6 ± 0.5 0 ± 0 0.7 ± 0.4 4.0 ± 0.9 7.9 ± 1.3 BCC 15.7 ± 1.1* 92.2 ± 1.2 0 ± 0 2.1 ± 0.6 0 ± 0 0.6 ± 0.3 1.1 ± 0.4 5.3 ± 1.3 SCC 16.7 ± 2.1* 92.6 ± 1.7 0 ± 0 1.9 ± 0.7 0 ± 0 0.4 ± 0.3 3.6 ± 1.1 7.1 ± 1.6 PS 21.9 ± 2.7* 83.8 ± 7.6 0 ± 0 1.5 ± 1.3 0.5 ± 0.4 2.1 ± 1.3 4.3 ± 2.7 8.9 ± 2.5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that high quantities of porphyrins were accumulated in a tumour implanted in the contralateral side of a topically treated tumour (data not shown), indicating that, if ALA is not transferred to remote sites by direct contact, an efflux of porphyrins to distant tumours may exist, very likely through the bloodstream. Similar results were obtained by Stringer et al (1996), when psoriasis plaques were treated with ALA and remote plaques displayed significant fluorescence, afterwards.…”
Section: Figuresupporting
confidence: 83%
“…This was investigated as there have been reports in the literature [44] which describe porphyrins in untreated areas of skin indicating that some systemic effect may be produced when ALA is applied topically. There was no evidence of this in this study however, indicating that application of a simple light occlusive dressing to the treatment area alone should be sufficient to prevent clinical cutaneous photosensitivity even when hyperaccumulating even greater amounts of PpIX with an iron chelating agent.…”
Section: Discussionmentioning
confidence: 99%